Identify Product Defects In The Injection Molding Process: Identifikasi Cacat Produk Pada Proses Injection Molding - Sulung Wibawansyah, Sulung Wibawansyah (Procedia of Engineering and Life Science, 2024)
Injection molding is a method of processing thermoplastic polymer seeds that are inserted into a hopper into a barrel then the material is pushed by a screw to enter the mold (mold). However, products produced by injection molding machines are sometimes still found defects in the product. Common defects include: Short shot, Flash, Sink mark, Flow mark, Black spot, Warpage and Colour streaks. And the most causative factors are materials that do not comply with production procedures, lack of checking on the control panel, mold design errors (mold). Keywords - Injection molding; defects; mold